Analisis Pengembangan Komponen Smart Village di Desa Limpung - Ananda Haniyuhana; Ary Setyo Wicaksono (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
Smart village is the development of a concept where village people are in a community that solves regional problems by utilizing their potential resources intelligently, wisely and efficiently and elevating local customs and culture, as well as applicable norms. Based on this explanation, of course the concept of a smart village cannot be separated from the five main components, namely smart governance, smart environment, smart economy, smart mobility, and smart tourism. As one of the villages implementing the smart village program, Limpug Village as one of the pilot villages for the implementation of the smart village program in Batang Regency has several problems that occur in implementing the smart village program which can be reviewed based on the five main components of the smart village concept. This research aims to determine the implementation of the smart village component in the implementation of the smart village program in Limpung Village. The method used in this study is a descriptive qualitative research method with data collection.